PHYSICAL AND CHEMICAL STUDIES OF THE OIL SLUDGE HYDROCARBON COMPOSITION AND THE PROSPECTS FOR THEIR USE IN THE TECHNOLOGY OF EXPANDED CLAY PRODUCTION - Bisenov Kylyshbai Aldabergenovich,; Narmanova Roza Abdibekovna,; Appazov Nurbol Orynbassaruly, (Academic Scientific Journal of Chemistry, 2020)
The article presents the results of gas chromatographic studies of the oil sludge hydrocarbon composition, physical and chemical and heat-producing properties, which enabled to assess the potential of oil sludge as raw materials, their assortment predisposition and possible manufacturability. It has been established that the main physical and chemical characteristics of the organic part from the averaged samples of oil sludge are similar in properties to raw materials for the production of kerosene-diesel fractions. The expediency of the use of oil sludge and weakly bloating clay materials in the production technology of the popular construction material – expanded clay is substantiated. The results of experimental studies on the development of light and porous heat insulating material by granulation method are presented herein. It is shown that oil sludge from a high viscous state is transferred to a loose conglomerate with a moisture content of 12–15% by co-mixing with finely dispersed sand dune, which ensures uniform distribution when mixed with the basic mass. The peculiarities of granules burning according to a specially developed mode without preliminary drying are considered. It has been established that the addition of oil sludge increases the organic content in the mixture, thereby intensifying the process of combustion, gas generation and bloating of the ceramic body, which will positively affect the technological parameters of obtaining а product. It is found that the proposed technology allows to obtain marketable products, which can be used efficiently. At the same time, the unconditional priority is given to waste-free technologies, as the most environmentally friendly.